Development of Geogebra Mathematics Learning Media on Exponential and Logarithmic Function Topics - Manurung, Hendra Cahyadi; Berutu, Jhosua; Turnip, Leonardo; Sinurat, Putra Paulus Glenn Niel; Suwanto, Fevi Rahmawati (Insitut Agama Islam Negeri Kerinci, 2024)
Information Technology really supports the teaching and learning process in mathematics learning, but in reality there are still very few teachers who use ICT in learning activities, even though if teachers use ICT in the learning process it can help students and teachers in learning mathematics. This research aims to determine the effect of multimedia mathematics learning assisted by the Geogebra application on students' conceptual understanding of exponential and logarithmic function material. The research method used is Research and Development (R&D), referring to the ADDIE development model. The subject of this research was carried out at SMA Negeri 1 SILIMAKUTA class X-3. The instruments used are student online response questionnaires, teacher online response questionnaires. Based on the results of testing the development of teaching materials assisted by Geogebra in learning exponential and logarithmic functions, from all aspects of statements from student response questionnaires and teacher responses, the average response percentage was 89.7%. Thus, the high percentage of student responses proves that the development of mathematics learning media assisted by Geogebra can increase students' understanding of concepts and can be used effectively and practically as an additional reference for mathematics learning media, especially material on exponential and logarithmic functions. The implication is that if every lesson uses the right media, it will increase students' learning motivation and improve their learning achievement.